การสกัดแยกและนำกลับโครเมตด้วยเยื่อแผ่นเหลว ที่พยุงด้วยเส้นใยกลวงในหอเดี่ยว - ไพศาล อภิณหพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
In this study, the factors affecting the extraction and the recovery of Cr(VI) in the form of chromate from aqueous solution through a hollow fiber supported liquid mebrane (HFSLM) were investigated. The organic solution as liquid membrane was ethyl trioctylamonium chloride (Aliquat) as a mobile carrier dissolved in kerosene with normal dodecanol as a modifier. The initial chromate concentration in aqueous feed solution was 100 ppm with using 1.0 mol/l NaOH solution as a stripping solution in recovery process. It is found from the experiments that extraction process occurred faster than recovery process. The extraction and the recovery of chromate were increased when the initial pH of feed solution or the flow rates of both aqueous solutions decreased. Consider the equilibrium of chromate in the aqueous phase and the membrane phase in batch experiment in presence of dodecanol, dodecanol improved the extraction and the recovery of chromate with the concentration of dodecanol not exceed 5 vol.%. The extraction and the recovery were independent on mode of flow direction, co-current and countercurrent operation. Transport of chromate in the extraction and the recovery processes was dropped when the concentration of chromate in feed phase was less than 60 ppm.